2012
DOI: 10.1089/jwh.2011.3224
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Cervical Cancer Diagnosis and Initiation of Treatment in the National Breast and Cervical Cancer Early Detection Program

Abstract: Objectives-To examine time intervals from cervical cancer screening to diagnosis and treatment initiation among low-income and uninsured women in the National Breast and Cervical Cancer Early Detection Program (NBCCEDP) during two consecutive time periods.Methods-We analyzed NBCCEDP data for women with abnormal Pap tests (n = 100,167), from which 1,417 invasive cervical cancers were diagnosed. We examined two time intervals for this study: diagnostic interval (time from abnormal Pap test to the date of definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…Screening abnormality rates observed across PROSPR are consistent with prior studies, 12,[15][16][17][18][19][20][21][22] yet the cross-organ perspective highlights the higher abnormality rate for breast cancer screening (10.5 % of individuals screened) relative to colorectal cancer screening using FOBT/FIT (4.7 % of individuals screened) or cervical cancer screening (7.9 % of Other factors may contribute to variation in the observed organ-specific abnormality rates, including the mix of breast imaging modalities with different operating characteristics, the sensitivity of different types of fecal occult blood tests, and the subjectivity of radiologist and cervical cytology interpretations, as well as differences in laboratory processing procedures. While UPenn was an early adopter of digital breast tomosynthesis, their abnormality rate was intermediate, between the rates observed for Dartmouth-BWH and VT.…”
Section: Discussionsupporting
confidence: 87%
“…Screening abnormality rates observed across PROSPR are consistent with prior studies, 12,[15][16][17][18][19][20][21][22] yet the cross-organ perspective highlights the higher abnormality rate for breast cancer screening (10.5 % of individuals screened) relative to colorectal cancer screening using FOBT/FIT (4.7 % of individuals screened) or cervical cancer screening (7.9 % of Other factors may contribute to variation in the observed organ-specific abnormality rates, including the mix of breast imaging modalities with different operating characteristics, the sensitivity of different types of fecal occult blood tests, and the subjectivity of radiologist and cervical cytology interpretations, as well as differences in laboratory processing procedures. While UPenn was an early adopter of digital breast tomosynthesis, their abnormality rate was intermediate, between the rates observed for Dartmouth-BWH and VT.…”
Section: Discussionsupporting
confidence: 87%
“…Studies examining outcomes associated with the BCCEDP have generally yielded favorable results with regard to cancer stage at diagnosis, 14 timeliness of care, [15][16][17][18] and treatment patterns. 6,19 In contrast, an earlier study reporting unfavorable outcomes in BCCEDP participants indicated that 71% of women who received mammography through the BCCEDP were symptomatic, and more than 50% of the women were diagnosed with late-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…The National Breast and Cervical Cancer Early Detection Program (NBCCEDP) provides funding to states for cervical cancer screening and treatment of uninsured and underinsured women contingent upon performance measures, including timely diagnosis and follow-up of women with abnormal cytology [20]. Despite improvements over time, the diagnosis interval (time between Pap testing and definitive diagnosis) across NBCCEDP sites remains somewhat longer for blacks compared to whites [21]. Another analysis found that black women had a higher percentage of no follow-up after two prior abnormal Pap tests [19].…”
Section: Discussionmentioning
confidence: 99%